Information needs and seeking behavior of Filipino online shopping app users - Reyes, James Martin A.
This study investigates the information needs and seeking behaviors of Filipino online shopping app users, particularly during the pandemic when reliance on ecommerce surged. It fills a gap in understanding Filipino consumers’ specific information needs, preferences, and behaviors on these platforms. The research aims to identify the types of information sought at different shopping stages, preferred formats, search methods, and decision-making factors. Utilizing qualitative methods, thematic analysis, and pattern coding, the study reveals that Filipino users prioritize product details, reviews, price comparisons, and social media input, preferring verified and reliable sources. Social media endorsements and influencer recommendations increasingly influence purchasing decisions. Technological and marketing strategies, such as mobile-friendly designs, social media integration, and personalized recommendations, significantly shape user experiences. Effective marketing strategies, including ads, loyalty programs, and exclusive sales, are crucial for user engagement. Continuous innovation and adaptive marketing are essential to maintain user interest and satisfaction. Filipino shoppers exhibit systematic behaviors, conducting thorough research and verification through various channels, emphasizing trust and authenticity. Challenges like price assessment and post-purchase issues are identified, highlighting the need for improved information transparency and consumer protection. Community engagement and personalization are key to addressing these challenges, as users demonstrate a proactive and adaptive approach to informed purchasing decisions.